Divalent Cu, Cd, and Pb Biosorption in Mixed Solvents - M. H. Al-Qunaibit (Bioinorganic Chemistry and Applications)
Dead dried Chlorella vulgaris was studied in terms of its performance in binding divalent copper, cadmium, and lead ions from their aqueous or 50% v/v methanol, ethanol, and acetone solutions. The percentage uptake of cadmium ions exhibited a general decrease with decrease in dielectric constant values, while that of copper and lead ions showed a general decrease with increase in donor numbers. Uptake percentage becomes less sensitive to solvent properties the larger the atomic radius of the biosorbed ion, and uptake of copper was the most affected. FT-IR analyses revealed stability of the biomass in mixed solvents and a shift in vibrations of amide(I) and (II), carboxylate, glucose ring, and metal oxygen upon metal binding in all media. ΔνCOO values (59–69 cm−1) confirmed bidentate metal coordination to carboxylate ligands. The value of νasCOO increased slightly upon Cu, Cd, and Pb biosorption from aqueous solutions indicating lowering of symmetry, while a general decrease was noticed in mixed solvents pointing to the opposite. M–O stretching frequencies increased unexpectedly with increase in atomic mass as a result of solvent effect on the nature of binding sites. Lowering polarity of the solvent permits variations in metal-alga bonds strengths; the smaller the metal ion, the more affected.